Assessing the Utility of Procedural Training for Pediatrics Residents in General Pediatric Practice - Ben-Isaac, Eyal (The Accreditation Council for Graduate Medical Education, 2013)
BACKGROUND: The Accreditation Council for Graduate Medical Education (ACGME) recommends that residents gain broad procedural competence in pediatrics training. There is little recent information regarding practice patterns after graduation. OBJECTIVE: We analyzed reported procedures performed in actual practice by graduates of a general pediatrics residency program. METHODS: We conducted an online survey from April 2007 to April 2011 of graduates of a single pediatrics program from a large children's hospital. Eligible participants completed general pediatrics residency training between 1992 and 2006. Graduates were asked about the adequacy of their training for each procedure, as well as the frequency of commonly performed procedures in their practice. As the primary analysis, procedures were divided into emergent and urgent procedures. RESULTS: Our response rate was 54% (209 of 387). General pediatricians rarely performed emergent procedures, such as endotracheal intubation, intraosseous line placement, thoracostomy, and thoracentesis. Instead, they more commonly performed urgent procedures, such as laceration repair, fracture or dislocation care, bladder catheterization, foreign body removal, and incision and drainage of simple abscesses. Statistically significant differences existed between emergent and urgent procedures (P < .001). CONCLUSIONS: In a single, large, urban, pediatrics residency, 15 years of graduates who practiced general pediatrics after graduation reported they rarely performed emergent procedures, such as endotracheal intubation, but more often performed urgent procedures, such as laceration repair. These results may have implications for ACGME recommendations regarding the amount and type of procedural training required for general pediatrics residents.